Art as Contextual Epistemology: A New Theoretical Perspective on Contemporary Avant-gardism in Africa (International Journal of Culture and Art Studies, 2020)
Art constitutes a framework for the generation of new knowledge that enables a sophisticated understanding of society. It is deconstructivist/interrogative thus leads to the creation of alternative narratives and realities derived from complex visual interpretation of the universe, societies and circumstances. In a cognitivist sense, beyond aesthetic emotions/visual appeal art constitutes an intellectual source of knowledge through in-depth analysis of form, content and context of any given artwork. The paper adopts discourse and iconographic analysis as methodologies to introduce a new uncovered phenomenon of Contemporary Avant-gardism in postcolonial African art based on knowledge generation tailored to enforce change. This is achieved by interrogating the ideologies, methodologies and visual configurations of the works of contemporary African artists such as El Anatsui, Olu Amoda, Brett Murray, Kudzanai Chiurai, Clem Akpang and others. Their works instigate new lines of inquiries/knowledge through a renewed but subtle bohemian approach to artifactuality and interpretation of contemporary Africa. The paper submits that by its evocative/expressive nature, art creates structures of knowledge through subjective and visual dialogues that foster knowing in different ways beyond language. And that in contemporary African art-space this new artistic ethos is deployed as a form of avant-gardism that underpins the rationale of African art created in the continent today.